Sosialisasi Sistem Pembuatan Sertifikat Otomatis dengan Metode System Development Life Cycle di PT PLN (Persero) Unit Induk Distribusi Aceh - Ira Zulfa; Eliyin, Eliyin; Muhammad Riski Aulia (Pusat Riset dan Inovasi Nasional, 2025)
This service presents the results of activities carried out at PT PLN (Persero) Aceh Distribution Unit, focusing on designing a web-based automatic certificate generation system using the System Development Life Cycle (SDLC) method. The main goal of the development of this system is to improve efficiency and effectiveness in the process of creating certificates that were previously done manually. Through the needs analysis, it was found that the current manual system resulted in delays and errors in the management of certificate data. The SDLC method was chosen to ensure that system development is carried out in a structured manner, from needs analysis to system maintenance.